CONTROL OF MOSQUITOES BY THE USE OF FISH IN ASIA WITH SPECIAL REFERENCE TO INDIA: RETROSPECTS AND PROSPECTS (Pengendalian Nyamuk dengan Penggunaan lkan di Asia dengan Rujukan Khusus ke India: Tinjauan Masa Lalu dan Masa Depan) - Somnath Chakraborty; Swaha Bhattacharya; Sajal Bhattacharya (Jurnal Manusia dan Lingkungan, 2008)
ABSTRACTFish have their greatest potential as biocontrol agents against the aquatic stages of mosquitoes and are used as a major component of the integrated vector control programme. Many countries in Asia including India have used mosquito larvivorous fish for the containment of mosquito borne diseases, especially malaria. Present review is an attempt to prepare a list of potential mosquito larvivorous fish used in different countries in Asia with special emphasis on India.ABSTRAKIkan berpotensi paling besar sebagai agen hayati terhadap stadia akualik nyamuk dan digunakan sebagai komponen utama dalam program pengendalian vektor terpodu. Banyak Negara di Asia termasuk India telah menggunakan ikan pemakan jentik untuk ,menanggulangi penyakit bawaan nyamuk. terutama malaria. Tinjauan pustaka ini mencoba memberikan suatu daftar jenis-jenis ikan pemakan jentik yang digunakan di berbagai Negara di Asia dengan penekanan khusus di India.